'I t's not going to be a one size fits all': a qualitative exploration of the potential utility of three drug checking service models in Scotland - Hannah Carver; Danilo Falzon; Wendy Masterton; Bruce Wallace; Elizabeth V. Aston; Fiona Measham; Carole Hunter; Harry Sumnall; Rosalind Gittins; Fiona Raeburn; Vicki Craik; Saket Priyadarshi; et al. (BMC, 2023)
Abstract Background Scotland currently has the highest rates of drug-related deaths in Europe, so drug checking services are being explored due to their potential role in reducing these deaths and related harms. Drug checking services allow individuals to submit presumed psychoactive drug samples for analysis, and then receive individualised feedback and counselling. This paper explores participants' views on the advantages and challenges of three hypothetical service models, to inform future service delivery in Scotland. Methods Semi-structured interviews were conducted with 43 people: 27 professional stakeholders, 11 people with experience of drug use, and five family members across three cities. Vignettes were used to provide short descriptions of three hypothetical service models during the interviews. Interviews were audio-recorded, transcribed and analysed using thematic analysis. Results Participants identified advantages and challenges for each of the three potential service models. The third sector (not-for-profit) model was favoured overall by participants, and the NHS substance use treatment service was the least popular. Participants also noted that multiple drug checking sites within one city, along with outreach models would be advantageous, to meet the diverse needs of different groups of people who use drugs. Conclusions Drug checking services need to be tailored to local context and needs, with a range of service models being possible, in order to meet the needs of a heterogeneous group of people who use drugs. Addressing issues around stigma, accessibility, and concerns about the potential impact of accessing drug checking on access to and outcomes of drug treatment, are essential for successful service delivery.